COVID-19: Fisiopatología y Características Observadas en la Atención de la Salud Oral en América. Una revisión sistemática. - Laquihuanaco Loza, Felipe (2024)
The new coronavirus (COVID-19) is the latest virus to cause a pandemic, which affected and altered the health of the world’s population. Dentists were no strangers to research on this topic, they reported and publishedthe oral signs that were presented. This research aims to collect and organize information on COVID-19from the stomatological point of view, 25 articles were taken from journals in Scholar Google, Scielo, Pubmed and Elsevier, which were thoroughly reviewed. The article is the result of a search for information on this disease and its clinical manifestations, with emphasis on those that occur in the oral cavity, since the functional and structural changes caused by this disease are primarily visualized in this organ, so that every health professional should consider the absolute necessity of looking at the mouth. Because COVID-19 has a predilection for ACE2 receptors, located in the tongue and salivary glands, the dental surgeon has a greater possibility of being a carrier of the disease.